Dampak Pinjaman Online Terhadap Mahasiswa di Kecamatan Cimanuk - Yuliani, Sipa Tias; R, Rahmawati; Mustakim, Usep Saepul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Online loans have become a popular financing alternative among students, especially in the current digital era. This research aims to analyze the impact of online loans on the consumer behavior of students in Cimanuk sub-district. The method used in this research is a quantitative survey involving 10 student respondents in Cimanuk sub-district. The research results show that easy and fast access to online loans encourages increased consumer behavior, where students tend to spend more money on non-priority needs such as entertainment and lifestyle. Apart from that, the findings also show that a lack of understanding of financial management and debt risk contributes to excessive consumerism. This research suggests the need for better financial education for students to help them manage loans and expenses wisely, so as to reduce the negative impact of online loans on their consumer behavior.